A Theoretical Modelling of the Associations between Housing and Family in the Light of Previous Research - abdolmajid nourtaghani; Parzhak Mohammad Pour; Abdollah Ebrahimi (صفه)
An understanding of the relationship between housing and the family is at the heart of any lifestyle-‎compliant housing design, without which no appropriate housing is feasible. Despite numerous studies about the relationship between housing and the family, no studies are found which systematically identifies and categorises this relationship. The present research intends to address the above shortcoming through a content analysis of previous research, and provide a theoretical model of how this relationship is. To do so, a qualitative approach was adopted, and using targeted sampling, an initial list of studies in this field was prepared, using library and electronic searches on resources dating from 1969 to 2018. In the final stage 77 relevant cases were shortlisted, and using content analysis, the housing and family components of the shortlist were extracted and coded. This was followed with the classification, interpretation and analysis of components, and a theoretical model of the relationship was presented. The results showed that, as emphasised by previous researches, spatial organisation is the most strongly associated aspect with the family, followed by physical characteristics, semantic orders and the behavioural settings. On the other hand, of the main five family features, the relationship between the socio-cultural characteristics of the family and housing was most emphasised, followed by the interactive-communicative, structural, economic-livelihood and demographic characteristics. To conclude, a theoretical model for the relationship between housing and family components was proposed. It is necessary to mention that this model needs to be put into test through field studies.‎